AFRICAN ECONOMIC AND POLITICAL SYMPTOMS POST WORLD WAR II - irma - sulistiowati (ISTORIA: Jurnal Pendidikan dan Sejarah, 2021)
Post-World War II did not only have an impact on countries that were the mother of the world power struggle. The country, which was only used as a puppet in the face of the war, was also heavily affected. The Asia-Africa region is a region that is largely a European colony. So that after the outbreak of World War II, countries in Asia and Africa experienced many political, economic and other spheres of life. The African region is the most devastated compared to the Asian region. Because all-natural resources have been exploited by Europeans on a large scale. There are plus and minus implications of the outbreak of World War II but what is certain is that the people of Africa must work very hard for a long time to restore all areas of human life so that they can live properly and prosperously.